Pretty baby - Kubica, Mary (Don Mills, Ontario : Mira, 2015)
Heidi Wood has always been a charitable woman: she works for a nonprofit, takes in stray cats. Still, her husband and daughter are horrified when Heidi returns home one day with a young woman named Willow and her four-month-old baby in tow. Disheveled and apparently homeless, this girl could be a criminalor worse. But despite her family's objections, Heidi invites Willow and the baby to take refuge in their home. Heidi spends the next few days helping Willow get back on her feet, but as clues into Willow's past begin to surface, Heidi is forced to decide how far she's willing to go to help a stranger.
Includes excerpt from the author's book: The good girl (pages [377]-380).
Keywords: Homeless persons -- Fiction; Teenage mothers -- Fiction; Infants -- Fiction; Married women -- Fiction; Middle class families -- Fiction; Honesty -- Fiction; Chicago (Ill.) -- Fiction; Psychological fiction; Suspense fiction